Production of 3-hydroxy-γ-decalactone, the precursor of two decenolides with flavouring properties, by the yeast Yarrowia lipolytica - Escamilla Garcia, Erandi (2009)
3-Hydroxy-γ-decalactone is the precursor of dec-2 and dec-3-en-4-olides which are valuable aroma compounds not yet produced. To promote the accumulation of this lactone, the yeast Yarrowia lipolytica was placed in different environmental conditions aiming at altering β-oxidation fluxes. The concentration of substrate, pH, aeration and dissolved oxygen level were modified. We observed an important accumulation at low aeration (0.40 molar yields) and, to a lesser extent, at lower pH (0.15). As oxygen played a key-role, we evaluated its effect at fixed dissolved oxygen and at the pH which was the most favourable to the biotransformation (pH 4.5). At 5% and 30% dissolved oxygen, yields reached 0.50. β-Oxidation fluxes are very dependent on the presence of oxygen and conditions of accumulation of 3-hydroxy-γ-decalactone with very high yields were identified. These results are an important step in the production of the two decenolides. Moreover, they show the high dependence of β-oxidation fluxes on environmental conditions and relate these conditions to the accumulation of intermediates, results that are of interest to all the processes using yeast on lipids or alkanes.